The carbon footprint of ambulatory gastrointestinal endoscopy - Lacroute, Joël; Marcantoni, Juliette; Petitot, Stéphane; Weber, Julien; Levy, Patrick; Dirrenberger, Bastien; Tchoumak, Irina; Baron, Mathilde; Gibert, Stéphanie; Marguerite, Sandrine; Huppertz, Jérôme; Gronier, Olivier; Derlon, Anne (Endoscopy, 2023)
Background Endoscopy is considered the third highest generator of waste within healthcare. This is of public importance as approximately 18 million endoscopy procedures are performed yearly in the USA and 2 million in France. However, a precise measure of the carbon footprint of gastrointestinal endoscopy (GIE) is lacking.Methods This retrospective study for 2021 was conducted in an ambulatory GIE center in France where 8524 procedures were performed on 6070 patients. The annual carbon footprint of GIE was calculated using “Bilan Carbone” of the French Environment and Energy Management Agency. This multi-criteria method accounts for direct and indirect greenhouse gas (GHG) emissions from energy consumption (gas and electricity), medical gases, medical and non-medical equipment, consumables, freight, travel, and waste.Results GHG emissions in 2021 were estimated to be 241.4 tonnes CO2 equivalent (CO2e) at the center, giving a carbon footprint for one GIE procedure of 28.4 kg CO2e. The main GHG emission, 45 % of total emissions, was from travel by patients and center staff to and from the center. Other emission sources, in rank order, were medical and non-medical equipment (32 %), energy consumption (12 %), consumables (7 %), waste (3 %), freight (0.4 %), and medical gases (0.005 %).Conclusions This is the first multi-criteria analysis assessing the carbon footprint of GIE. It highlights that travel, medical equipment, and energy are major sources of impact, with waste being a minor contributor. This study provides an opportunity to raise awareness among gastroenterologists of the carbon footprint of GIE procedures.